Faktor – faktor yang berhubungan dengan kejadian Abortus di RSUD Sungai Lilin kabupaten Musi Banyuasin tahun 2022 - Sundari, Penti; ismed, syarifah; Afrika, Eka (NHM PRESS, 2024)
The Maternal Mortality Rate in Indonesia was recorded at 177 per 100 thousand live births in 2017. This ratio is better than dozens of previous years of more than 200 deaths per 100 thousand live births. Abortion is one of the complications of pregnancy with a percentage of 15-20% with 80% occurring in the first trimester (<13 weeks) and very few occurring in the second trimester. The purpose of this study was to determine the factors associated with the incidence of abortion related to maternal age, parity, history of abortion and the distance between pregnancies simultaneously with the incidence of abortion at Sungai Lilin Hospital, Musi Banyuasin district in 2022. The research method used an analytical survey with a cross sectional approach. The population in this study were all pregnant women who were treated in the midwifery room at Sungai Lilin Hospital, Musi Banyuasin Regency. In January-December 2022 there were 380 people. The research sample of 79 respondents was taken using simple random sampling technique. The research instrument uses a checklit sheet. Data analysis used univariate and bivariate analysis using the chi square test. The results of the univariate study showed that of the 79 respondents who had an abortion, 56 respondents (70.9%) and 23 respondents (29.1%) who did not experience an abortion. From the bivariate analysis using the chi square test, the results showed that there was a relationship between maternal age (p value = 0.013), parity (p value = 0.008), history of abortion (p value = 0.023), and gestational spacing (p value = 0.003 with the incidence of abortion at Sungai Lilin Hospital, Musi Regency in 2022. It is hoped that the results of this study can be an illustration for the hospital to be able to further improve health services, especially regarding pregnant women patients with abortion events